The Effect of the Number of Tiktok Account Followers in Determining the Number of Sales - Syahdilia Tri Devitasa (Jurnal Manajemen Bisnis dan Pariwisata, 2025)
The development of technology is increasingly rapid, with technology social media was born. The purpose of this study is to find out what Tiktok is, the influence of the number of followers of Tiktok accounts in determining the number of sales, disadvantages and advantages of using the Tiktok application as a means of promotion. The research method used is a quantitative method that is a type of systematic research on each part and event and its cause-and-effect relationship. The results of this research analysis show that the number of followers of Tiktok accounts has a positive effect on determining the number of sales. However, there are other factors that influence, for example, such as price, quality of goods, and uploading good content that can attract buyers. Business owners are advised to use Tiktok regularly to market their products. It is hoped that business owners will use Tiktok as well as possible so that their sales will increase.